Law Enforcement Against Perpetrators of Imported Clothing Smuggling as an Economic Crime to Enhance the National Economy - Dini Ramdania; Edi Setiadi; Dini Dewi Heniarti; Ifeanyi M. Nwokeocha; Anurag Hazarika (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Smuggling at present has reached an alarming level, no longer merely constituting an economic offense but amounting to an economic crime. The smuggling of goods, particularly textiles, has caused significant losses and adversely affected the national economy. The state’s response in establishing a special task force to address smuggling has, in practice, been unable to eradicate the influx of smuggled goods in a comprehensive manner. Measures undertaken thus far have proven inadequate in resolving the problem. The sanctions provided under Law No. 17 of 2006 on Customs, in the form of criminal penalties and/or fines, are considered insufficient if the objective is to recover the losses suffered by the state, both in terms of taxation and other economic consequences. In reality, such sanctions have failed to create a deterrent effect, leaving the state in a position of continual loss.